A successful comparison between a non-invasive measurement of local profiles during drying of a highly shrinkable food material (eggplant) and the spatial reaction engineering approach. (October 2018) - Putranto, Aditya; Chen, Xiao Dong
Abstract: A reliable mathematical model is useful for predicting internal profiles inside materials during drying. In this study, for the first time, the spatial reaction engineering approach (S-REA) is employed to model the local profiles of food materials during drying. The REA is applied as the local rate of phase change and combined with a set of equations of conservation of heat and mass transfer to yield the spatial profiles of temperature and concentration during drying. The S-REA predictions are benchmarked against the Magnetic Resonance Imaging (MRI) data. The study indicates that the S-REA is applicable to model the internal profiles inside food materials during drying. The S-REA predictions also show closer agreement towards the experimental data than the effective diffusion model. While the S-REA predictions are accurate, it requires minimum number of experiments to generate the drying parameters. The S-REA has contributed to better analysis of transport phenomena inside food materials during drying through generation of local profiles. The S-REA predictions can potentially be implemented to interpret the sensory and quality matters during drying. Highlights: The S-REA predicts accurately the local profiles during drying as benchmarked towards MRI measurement. The local profiles generated by the S-REA assist in explaining complex interrelationships among variables during drying. The S-REA predictions are useful to describe the quality matters during drying.